Exploratory study: The needs and care of children with cerebral palsy who have drooling (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: The purpose of this study was to explore the needs and care and expectations of parents of children with CP who are drooling.Methods: This qualitative research with phenomenology approach was conducted at YPAC Semarang in September 2016. Data collection was done by in-depth interviews with 6 maternal participants selected through purposive sampling and 1 rehabilitation medical doctor and 1 teacher as a triangulation participant. Data analysis was done according to Collaizi steps.Results: This research produced ten themes: need to overcome drooling; Overcome feelings of sadness, embarrassment, brokenness, low self-esteem, hurt, sensitivity, offended when children are bullied, can not bear, feelings of refusal, acceptance, fear and self-blame; Overcome child shame; Financing for child therapy; Strength, sense of spirit, gratitude, patience and endeavor; Accepted by society and concern by the government; Environmental modification; Coping with drooling; Poor understanding of mothers; and Mother's expectation of foundation and government supported health services, education, and child's independence.Conclusion: Optimizing the fulfillment and care needs of CP children with grade IV and V drooling involves strategies to overcome drooling using drooling absorbents and long-term care.